The Determining Factors of Foreign Direct Investment (FDI) Inflows: Empirical Studies from the Southeast Asian Countries - Iksan, Muhamad; Konishi, Tetsu (LPPM Universitas Lampung, 2023)
The purpose of the study estimates the possible causal relation between direct foreign investment with intertwined political and economic factors ranging from the investment climate reform initiative, tax policy conducted by the government, size of the government, and political institution. The sample of this study consists of ten countries in the Southeast Asia region. Our study utilizes time series data of 11 years from 2010 to 2020, to empirically tested three proposed hypotheses by using panel data regression analysis. Our statistical results show that determinants of direct foreign investment can be uncovered through economic rather than political factors. This study provides a negative relationship between the political institution factor (proxied by the veto player) and FDI inflow. On the contrary, the EODB score does not affect FDI inflow by controlling covariates. Moreover, our study could not provide robust evidence that an effective average tax rate could affect the FDI inflow which is contrary to literature expectation. However, our causal inference may suggest that previous FDI inflow is the best predictor for the FDI inflow.